The role of regional inspectorates in local government procurement oversight - Amrie Firmansyah; Septian Ventiarso (Akuntansiku, 2026)
Public procurement at the local government level represents a high-risk area of public expenditure due to its vulnerability to inefficiency and irregularities, thus requiring effective internal oversight. Local inspectorates, as part of the Government Internal Supervisory Apparatus (APIP), are expected to play a strategic role in ensuring accountability and risk prevention throughout the procurement cycle. However, audit findings consistently indicate that internal oversight has not yet functioned optimally. This study aims to map and synthesize empirical evidence on the effectiveness of local inspectorates in overseeing government procurement and to identify key challenges constraining their role. Using a scoping review approach, the literature was systematically searched through Google Scholar and Publish or Perish. The initial identification yielded 188 articles published between 2015 and 2026. Following title and abstract screening and full-text assessment based on inclusion and exclusion criteria, six empirical studies were identified as directly and substantively relevant to the role of inspectorates in local government procurement oversight. Thematic synthesis reveals three dominant findings: the continued dominance of compliance-based (post-audit) oversight; limited implementation of risk-based and probity audits; and insufficient involvement of APIP across the entire procurement cycle. These findings indicate that procurement oversight remains largely reactive and has not been systematically institutionalized as a preventive risk management mechanism. This study contributes by providing a focused, methodologically sound map of the empirical literature on local inspectorates’ roles in procurement oversight and by offering a conceptual basis for strengthening internal control policies in local government procurement.